Effectiveness of Adaptive Blended Digital Technology Learning to Improve Learning Outcomes of Digital Native Learners in COVID-19 Pandemic Situation - Netwong, Titiya (ASEAN Journal of Education, 2023)
The objectives of this research were (1) to study the students’ learning styles to create adaptive blended digital technology learning. (2) To study the effect of adaptive blended digital technology learning to improve learning outcomes of the digital native learners in the COVID-19 pandemic situation and (3) to study the pretest and posttest results with adaptive blended digital technology learning. The sample group consisted of 49 undergraduate students in the Digital Literacy course in the second semester of the 2020 academic year, Suan Dusit University. The research instruments were (1) the perceptual learning style preference questionnaire, (2) learning management plans using adaptive blended digital technology and (3) the questionnaire for learning outcomes with innovative learning. The data obtained were analyzed using frequency, percentage, mean, standard deviation and t-test dependent. The results of the study were as follows: (1) The significant learning style preference of the sample group were Audio Learning Style (ALS), Group Learning Style (GLS) and Kinesthetic Learning Style (KLS), respectively. The sample group use of digital technology for learning was at a high level. (2) The learning outcomes in the learning innovation of the sample group were at the highest level when they were sorted on a descending order to technology utilization, digital media creation and intellectual skills. (3) the learning outcomes of the sample group before and after the study showed significant difference at.05; the learning outcomes after the experiment (M = 4.21, SD = 0.43) were higher than before (M = 3.12, SD = 0.71).